Trends in food and beverage purchases in informal, mixed, and formal food outlets in Mexico: ENIGH 1994–2020 - Domínguez-Barreto, Ana Paula; Farah, Irene; López-Olmedo, Nancy; Perez-Ferrer, Carolina; Ramírez-Toscano, Yenisei; Barrientos-Gutiérrez, Tonatiuh; Stern, Dalia (Frontiers in Public Health, 2023)
Background The retail food environment in Mexico is characterized by the co-existence of both, formal and informal food outlets. Yet, the contribution of these outlets to food purchases over time has not been documented. Understanding the longitudinal trends where Mexican households purchase their foods is critical for the development of future food retail policies. Methods We used data from Mexico’s National Income and Expenditure Survey from 1994 to 2020. We categorized food outlets as formal (supermarkets, chain convenience stores, restaurants), informal (street markets, street vendors, acquaintances), and mixed (fiscally regulated or not. i.e., small neighborhood stores, specialty stores, public markets). We calculated the proportion of food and beverage purchases by food outlet for each survey for the overall sample and stratified by education level and urbanicity. Results In 1994, the highest proportion of food purchases was from mixed outlets, represented by specialty and small neighborhood stores (53.7%), and public markets (15.9%), followed by informal outlets (street vendors and street markets) with 12.3%, and formal outlets from which supermarkets accounted for 9.6%. Over time, specialty and small neighborhood stores increased 4.7 percentage points (p.p.), while public markets decreased 7.5 p.p. Street vendors and street markets decreased 1.6 p.p., and increased 0.5 p.p. for supermarkets. Convenience stores contributed 0.5% at baseline and increased to 1.3% by 2020. Purchases at specialty stores mostly increased in higher socioeconomic levels (13.2 p.p.) and metropolitan cities (8.7 p.p.) while public markets decreased the most in rural households and lower socioeconomic levels (6.0 p.p. & 5.3 p.p.). Supermarkets and chain convenience stores increased the most in rural localities and small cities. Conclusion In conclusion, we observed an increase in food purchases from the formal sector, nonetheless, the mixed sector remains the predominant food source in Mexico, especially small-neighborhood stores. This is concerning, since these outlets are mostly supplied by food industries. Further, the decrease in purchases from public markets could imply a reduction in the consumption of fresh produce. In order to develop retail food environment policies in Mexico, the historical and predominant role of the mixed sector in food purchases needs to be acknowledged.